2014
DOI: 10.1073/pnas.1406619111
|View full text |Cite
|
Sign up to set email alerts
|

Immature truncated O-glycophenotype of cancer directly induces oncogenic features

Abstract: Aberrant expression of immature truncated O-glycans is a characteristic feature observed on virtually all epithelial cancer cells, and a very high frequency is observed in early epithelial premalignant lesions that precede the development of adenocarcinomas. Expression of the truncated O-glycan structures Tn and sialyl-Tn is strongly associated with poor prognosis and overall low survival. The genetic and biosynthetic mechanisms leading to accumulation of truncated O-glycans are not fully understood and includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
275
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 266 publications
(289 citation statements)
references
References 65 publications
14
275
0
Order By: Relevance
“…For example, Gao et al reported that loss of intestinal O‐glycans significantly promotes spontaneous duodenal tumours in mice and aberrant O‐glycosylation may serve as critical determinants of duodenal cancer risks49; however, Bergstrom et al unexpectedly found that, although mice deficiency in intestinal O‐glycans developed typical colonic cancers, it was indeed dependent on colitis rather than aberrant O‐glycosylation 50. In addition, several studies showed that direct deletion of Cosmc in pancreatic cancer cell lines induces classical oncogenic features, which is also in agreement with our findings 35, 51. But Huang et al reported that forced overexpression of Cosmc in human colorectal cancer cell lines significantly increases malignant behaviours, whereas knockdown of Cosmc suppresses oncogenic features 52.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For example, Gao et al reported that loss of intestinal O‐glycans significantly promotes spontaneous duodenal tumours in mice and aberrant O‐glycosylation may serve as critical determinants of duodenal cancer risks49; however, Bergstrom et al unexpectedly found that, although mice deficiency in intestinal O‐glycans developed typical colonic cancers, it was indeed dependent on colitis rather than aberrant O‐glycosylation 50. In addition, several studies showed that direct deletion of Cosmc in pancreatic cancer cell lines induces classical oncogenic features, which is also in agreement with our findings 35, 51. But Huang et al reported that forced overexpression of Cosmc in human colorectal cancer cell lines significantly increases malignant behaviours, whereas knockdown of Cosmc suppresses oncogenic features 52.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, hypermethylation in Cosmc, which would result in Cosmc gene silencing, was reported in pancreatic tumours and Tn syndrome expressing truncated O‐glycans 26, 35. We therefore conducted a MALDI‐TOF spectrometry methylation analysis of Cosmc and T‐synthase in another pair of Tn‐positive and Tn‐negative cancer tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of aberrant forms of O-glycans such as Tn and sTn is frequently observed in breast cancer and considered to play a causal role in tumor development (7). In this study, we unexpectedly found that loss of core 1-derived O-glycans and subsequent expression of Tn in mammary epithelial cells delayed the onset and progression of breast tumor based on results from two wellestablished spontaneous breast tumor mouse models.…”
Section: Discussionmentioning
confidence: 62%
“…Instead, Radhakrishnan et al (4) found that in 38% (13 of 34) pancreatic cancer tissue samples the COSMC promotor was methylated. Furthermore, promotor methylation correlated with loss of C1GalT1 expression and the presence of Tn antigen.…”
mentioning
confidence: 97%
“…The ground-breaking work by Radhakrishnan et al (4) in PNAS has taken advantage of a novel technique they developed to identify sites of O-glycan addition to proteins (5,6), to provide evidence that truncation of O-glycans induces oncogenic features, such as enhanced growth and invasion. The results are remarkable not only because they indicate that O-glycans play a critical role in regulating growth and adhesive properties of cells, but because they also demonstrate that multiple different properties associated with an enhanced malignant phenotype are affected when O-glycans are truncated.…”
mentioning
confidence: 99%